Ascorbic acid derivative DDH-1 ameliorates psoriasis-like skin lesions in mice by suppressing inflammatory cytokine expression - Kosuke Kitahata; Kazuhiko Matsuo; Yuta Hara; Takanori Naganuma; Naoki Oiso; Akira Kawada; Takashi Nakayama (Elsevier, 2018)
Psoriasis is a chronic inflammatory skin disease in which inflammatory cytokines play a major role in its pathogenesis. Because DDH-1, a novel amphipathic ascorbic acid derivative, has been recently shown to reduce inflammatory cytokine expression in human keratinocytes in vitro, we investigated its effect on imiquimod-induced psoriasis-like skin lesions in C57BL/6 mice. We first found that IL-1β and TNF-α mRNA expression was significantly decreased in the skin lesions treated with DDH-1. Furthermore, cutaneous administration of DDH-1 ameliorated psoriasis-like skin lesions. These results suggest that DDH-1 may be effective in the prevention and supplemental treatment of psoriasis. Keywords: Ascorbic acid derivative, Psoriasis, Inflammatory cytokine